2004
DOI: 10.1111/j.1472-8206.2004.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: the evolution of antidepressant mechanisms

Abstract: Present antidepressants are all descendents of the serendipitous findings in the 1950s that the monoamine oxidase inhibitor iproniazid and the tricyclic antidepressant imipramine were effective antidepressants. The identification of their mechanism of action, and those of reserpine and amphetamine, in the 1960s, led to the monoamine theories of depression being postulated; first, with noradrenaline then 5-hydroxytryptamine being considered the more important amine. These monoamine theories of depression predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 200 publications
1
111
0
Order By: Relevance
“…The brain regions analyzed are shown in Figure 1. The majority of brain regions were chosen based on those that have been implicated in major depression from human neuroimaging studies and from preclinical studies involving lesions and prior IEG studies (Drevets, 1999(Drevets, , 2000(Drevets, , 2001Kirby and Lucki, 1997;Ongur and Price, 2000;Ronan et al, 2000;Slattery et al, 2004;Sumner et al, 2004). These studies have revealed that numerous brain regions that have previously not been implicated in depression seem to play roles; therefore, we also determined to examine a number of other brain regions, at the same bregma coordinates as those implicated in depression.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain regions analyzed are shown in Figure 1. The majority of brain regions were chosen based on those that have been implicated in major depression from human neuroimaging studies and from preclinical studies involving lesions and prior IEG studies (Drevets, 1999(Drevets, , 2000(Drevets, , 2001Kirby and Lucki, 1997;Ongur and Price, 2000;Ronan et al, 2000;Slattery et al, 2004;Sumner et al, 2004). These studies have revealed that numerous brain regions that have previously not been implicated in depression seem to play roles; therefore, we also determined to examine a number of other brain regions, at the same bregma coordinates as those implicated in depression.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…Despite the availability of a number of successful antidepressants, the pathology of depression remains unclear. All current drugs have a delayed onset of action and a primary mechanism of action to increase monoamine levels in the brain (see Slattery et al (2004) for a review). Although chronic administration of antidepressants is required for clinical benefit, acute IEG induction can give insight into their mechanisms as it reflects longer-term alterations in cellular phenotype and provides insight into the brain regions affected by antidepressants (for reviews see Beckmann and Wilce, 1997;Dragunow and Faull, 1989;Herdegen and Leah, 1998;Herrera and Robertson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For the past 30 years, the prominent theories of mood disorders pointed to the pathological evidence of decreased monoamine levels, including the low 5-HIAA found in suicide victims. 3,4 Indeed, the monoamine oxidase inhibitors since iproniazide, the tricyclic antidepressants (TCAs), the selective serotonin reuptake inhibitors (SSRIs) and the serotonin/noradrenaline reuptake inhibitors (SNRIs) are all causing elevation of synaptic monoamine levels.…”
Section: Introductionmentioning
confidence: 99%
“…1 Pharmacotherapy using tricyclic antidepressants, including imipramine, clomipramine, amitriptyline and nortriptyline, 2 has been an essential constituent of antidepressive treatment for over 30 years. 3 The typical tricyclic antidepressant imipramine is metabolized by cytochrome P450 enzymes.…”
Section: Introductionmentioning
confidence: 99%